Electrochemical Study of Corrosion Inhibition Action of Sulphadoxine and Pyrimethamine on Mild Steel in Acidic Medium - Akpan, I. A; Offiong, N. O (International Journal of Chemical and Process Engineering Research, 2014)
The corrosion inhibition action of sulphadoxine and pyrimethamine, which is being sold under the trade name “Antimal” as a single antimalarial drug was used as low cost and eco-friendly inhibitor for acid corrosion of mild steel monitored by means of an electrochemical technique at room temperature (30oC). It was found that the polarization resistance of the inhibitor was directly proportional to the concentration of the inhibitor –making the metal more resistant to corrosion at higher inhibitor concentrations. Also, the inhibition efficiency was found to increase with rise in concentration of the inhibitor. The experimental data were found to fit better for Temkin isotherm which illustrates multilayer chemisorption. However, significant correlation (R2 = 0.76) was found for Frumkin isotherm indicating possible amphiphilic interactions from alkyl substituents on the inhibitor molecules.